2004
DOI: 10.1073/pnas.0308474100
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the zebrafish choroideremia gene encoding Rab escort protein 1 devastates hair cells

Abstract: To identify genes important for hair-cell function, we conducted a mutagenic screen in zebrafish. Larvae from one mutant line, ru848, were unresponsive to acoustic stimuli and unable to balance. The mutation results in a 90% reduction in hair-cell number and partial retinal degeneration by 5 days postfertilization. We localized the recessive ru848 mutation by positional cloning to the zebrafish homolog of the human Choroideremia gene, which encodes Rab escort protein 1. This protein is essential for the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 28 publications
6
69
0
Order By: Relevance
“…The displacement of the stimulus probe was always set at 5.8 μm during the experiments unless otherwise specified in the text. The probe tip was placed against the skin at the posterior end of the otic vesicle (pointing to the saccular otolith) and provided linear oscillatory motion along an axis 20 o off the longitudinal axis of the fish body (Corey et al 2004;Starr et al 2004). The parameters such as size, angle, and location of the stimulus probe affecting microphonic responses were kept constant for all recordings reported herein.…”
Section: Electrophysiology Rigmentioning
confidence: 99%
See 3 more Smart Citations
“…The displacement of the stimulus probe was always set at 5.8 μm during the experiments unless otherwise specified in the text. The probe tip was placed against the skin at the posterior end of the otic vesicle (pointing to the saccular otolith) and provided linear oscillatory motion along an axis 20 o off the longitudinal axis of the fish body (Corey et al 2004;Starr et al 2004). The parameters such as size, angle, and location of the stimulus probe affecting microphonic responses were kept constant for all recordings reported herein.…”
Section: Electrophysiology Rigmentioning
confidence: 99%
“…Particularly, Fay's shaker apparatus was used to accelerate the whole fish, resulting in acceleration of the inner ear, to simulate underwater acoustic particle motion (Fay 1984;. In this study, we adapted a stimulus probe from Corey et al (2004) and Starr et al (2004) to provide focal stimulation directly to the inner ear of zebrafish embryos or larvae instead of accelerating the entire fish body. The oscillatory motion of the probe tip caused the vibration of the posterior wall of the otic vesicle, leading to auditory transduction of hair cells in the inner ear.…”
Section: Factors Affecting the Microphonic Potential Recordingmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, two genes essential for the function of photoreceptor cells and associated with retinal dystrophy have recently been identified. The mutation in the zebrafish orthologue of the human choroideremia gene, which encodes the Rab escort protein-1 and is responsible for a human disease marked by slow-onset degeneration of rod photoreceptors and retinal pigment epithelial cells, was recently identified (Starr et al, 2004). Subsequent analysis suggested that the gene function is necessary in the RPE, and the photoreceptor deficit in secondary to this alteration (Krock, et al, 2007).…”
Section: Photoreceptor Dystrophiesmentioning
confidence: 99%